One world - Mitchner, E. A.; Tuffs, R. Joanne (Renee Joanne), 1944- (Edmonton : Reidmore Books, 1989)
Basic resource in Alberta for Social Studies 20, ca. 1989-2008.
Keywords: Human geography; Human ecology; Circular 14 titles